The interrelationships between boutique store atmosphere, customer satisfaction, store loyalty and repurchase intention - a study of females in the North-West Province - BM van Niekerk; DJ Petzer; LT de Beer (The Retail and Marketing Review, 2016)
The global fashion retail industry has been characterised by fierce competition and therefore retailers face increasing pressure to differentiate themselves from competitors by catering for the ever-evolving needs, wants and desires of customers. Customers are becoming increasingly more sophisticated and individualistic and turn to small speciality retailers such as boutiques to provide unique and tailored retail experiences. It is therefore important for boutiques to be aware of and actively manage their store atmosphere, as it contributes to a positive retail experience. It is professed that a customer who positively experiences a retailer’s store atmosphere will feel more satisfied and will return with the hope of receiving a similar experience. Once the customer returns, the possibility arises that the customer may become store loyal and the probability of developing positive repurchase intentions becomes real. The primary objective of this study is to investigate the interrelationships of boutique store atmosphere on customer satisfaction, store loyalty and repurchase intention at boutiques. A descriptive research design was followed and self-administered questionnaires were fielded. Judgemental, convenience and quota sampling were used to select a sample of 400 respondents. A total of 361 questionnaires were suitable for analysis. The results indicate that store atmosphere has a large direct influence on both customer satisfaction and store loyalty, albeit with no direct influence on repurchase intention. A medium indirect effect was realised for both mediating relationships between store atmosphere and repurchase intention with customer satisfaction and store loyalty as respective mediators. Conclusion and recommendations are subsequently presented.